Some issues about intellectual property management in scientific research and technology development in Vietnam - Khong Quoc Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Aspects of intellectual property (IP), the effectiveness of scientific research and technological development is evaluated based on the intellectual assets created to achieve the objectives in terms of quality, quantity and commercialization of those assets. Intellectual property management in scientific research and technological development helps to achieve that target. However, the approach and content of IP management activities in scientific research and technological development are still controversial. The article clarifies the approach, proposes contents of IP management in scientific research and technology development to improve the efficiency of these activities in Vietnam. Code: 22031601